National Education Policy and Its Implementation in Elementary Schools - Rosmawiah, Rosmawiah (Jurnal Ilmiah Kanderang Tingang, 2023)
Education is a universal humanitarian phenomenon which if true its activities will foster the multidimensional development of basic human abilities. The direction of educational attention is more on students, namely those who are able to optimize their potential as individual human beings. To achieve this goal, the role of various parties is needed, especially policy makers, in this case the government and institutions directly related to education. The basic direction of national education policy attention is Elementary Schools because they are the initial institutions for the formation of humans towards optimal intelligence. National education policy in this context is more on its implementation in basic education institutions.